Haptic Illusions and Imagined Agency: Felt Resistances in Sonic Experience. - Peters, Deniz (Contemporary Music Review, 2013)
Sounds appear to hold a resistance within themselves, a resistance different from the physical resistance one engages with when playing a musical instrument. I here argue that this felt resistance or tactility can beheard inthe sounds cross-modally by listeners and experienced despite the transparency of instrumental actions and effort an expert performer may achieve. I start by distinguishing the cross-modal phenomenon from instrumental resistance and describe how in dancers' improvised performances with a virtual spatial musical instrument developed and used in the ‘Embodied Generative Music’ project it occurs in a particularly exposed way; I then seek to conceptualise its experience, relating it to perceptive phenomena and concepts of embodied perception; in a third step, I ponder its role in the forming of agency, imagined agency, and expression within musical experience and performance. The text is supported by video clips which appear as supplementary material accessible online via the article's Supplementary tab on the Taylor & Francis website (http://www.tandfonline.com/loi/gcmr).